Digit ratio (2D:4D) and performance in elite rugby players - Bennett, M.; Manning, J. T.; Cook, C. J.; Kilduff, L. P. (Journal of Sports Sciences, 2010)
The relative length of the second and fourth digits (2D:4D) is a putative marker for prenatal testosterone. Low 2D:4D has been reported to correlate with high performance in sport in general. Here, for the first time, we examine the relationship between 2D:4D and performance in elite rugby players. The 44 players (28 forwards, 16 backs) were drawn from the Ospreys Rugby Union Club and 44 age-matched controls. The measures of performance comprised age-adjusted number of international performances (caps) for Wales, a comparison of coaches' first-choice League team with others, and the number of tries scored by backs in club matches. Compared with controls, players were larger and had lower 2D:4D for the right and left hand. With regard to number of caps, players with low 2D:4D in their right hand and low right 2D:4D compared with their left (right - left 2D:4D difference) had high numbers of caps. First-choice players did not differ significantly from second-choice players in their 2D:4D but they did have a lower right - left 2D:4D difference than second-choice players. Low right 2D:4D and low right - left 2D:4D difference were significantly linked with large numbers of tries. We conclude that low right 2D:4D and low right - left 2D:4D difference are predictors of high rugby performance.